Zhilenko I. R. M. P. Artsybashev carries on traditions of A. P. Chekhov - Zhilenko I. R. (Philological Treatises, 2020)
The article focuses on the aspects of creation of A.P. Artsybashev which continue traditions of A.P. Chekhov, points out similarities within poetics, dominant elements of style, thematic diversity etc.